EFFICIENCY AND RELIABILITY ANALYSIS OF SOLAR POWER GENERATING SYSTEM FOR 450 VA APPLICATION IN SIRUAR VILLAGE, TOBA REGENCY - Nugraha, Satria; Wibowo, Pristisal; Siagian, Parlin (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the efficiency and reliability of a solar power generation system (PLTS) for household applications with a power of 450 VA in Siruar Village, Toba Regency. PLTS is a potential solution to meet electricity needs in remote areas that are difficult to reach by conventional electricity networks. This study includes evaluation of solar panel performance, energy conversion efficiency, and analysis of system reliability in providing a stable electricity supply. The research method involves collecting technical data from the installed PLTS system, analyzing energy efficiency using input and output power parameters, and measuring reliability indices such as duration of interruption and frequency of blackouts. The results of the study show that the PLTS system is able to produce sufficient electrical energy for basic household needs, with energy conversion efficiency reaching 89.74% to 97.22% and a level of reliability that meets operational standards. This study contributes to supporting the development of renewable energy in rural areas and becomes a reference in planning and optimizing similar PLTS systems in the future.